Implikasi Wacana Kampanye Anti Kekerasan Seksual Terhadap Glorifikasi Pelaku Kejahatan Seksual Di Media Online - Riska Mutiah; Athik Hidayatul Ummah (University of Muhammadiyah Malang, 2021)
The spread of anti-sexual violence campaigns on social media such as the #metoo, #kitaAgni and #namabaikkampus movements raises public awareness about the issue. This can be seen in the rejection and public anger related to the news about the glorification of sex offenders who incidentally was a public figure when he was released from prison which was published in online media. Therefore, this article examines the implications of anti-sexual violence discourse on the glorification of sexual offenders in online media by using critical discourse analysis by Sara Mills which focuses on the position of subject-object and the position of readers in the news. This article shows that there is a discourse battle between the sex offenders who show resistance while the public continues to reject it simultaneously.